Adolescent instruction in the ESL context: situational realism and linguistic realism in material selection / S. Kunaratnam Sita Raman and Evelyn Sharminnie S. Vasuthavan - Sita Raman, S. Kunaratnam; Vasuthavan, Evelyn Sharminnie S. (2011)
Youths today have come a long way away from conforming to ideals that have become so stereotype in society. The impulsive, defiant and often rebellious nature of youths especially in the adolescent stage needs to be addressed by all quarters of society, especially educators. In the ESL context, it is the responsibility of language instructors to select instructional materials that help learners connect with the lesson when designing classroom activities and tasks. Most adolescents would feel motivated only when they are able to connect what is laid down before them to real life. Learners therefore would need genre related specialized knowledge to catalyze their learning. This paper draws the attention of language instructors to linguistic and situational realism, in an effort to enhance communicativeness in the selected material. This is done by identifying weaknesses in Linguistic realism' and 'Situational realism' in dialogues presented in the texts. Justifications are made based on the context, setting and background of the interlocutors. The terms Linguistic realism' and 'Situational realism' are clearly defined to help language instructors see the imminence of adopting, adapting and authenticating instructional materials to not only encourage but also to attract, enthuse and encourage active learner participation in classroom activities.